The Shifting Meaning of Istiṭa‘ah in Performing Hajj for the Bone People in the Perspective of Islamic Law - Bustanul Arifin, Nursyirwan; Keri, Ismail; Said, Ali; Kiramang, Khaeruddin; Khaironi, Ghazanul Fikri (Samarah: Jurnal Hukum Keluarga dan Hukum Islam, 2023)
The community’s understanding of istiṭa’ah (ability) has shifted and narrowed in meaning towards the economic aspect. This study aims to describe the concept of istiṭa’ah as understood by the people of Bone, South Sulawesi, the factors that cause the narrowing of the meaning of istiṭa’ah, and the economic contents that influence the meaning of istiṭa’ah. This study used a qualitative method using the lughawi approach and Islamic law as an analytical tool. Data were collected by means of in-depth interview and literature review. This study found that the people of Bone have interpreted istiṭa’ah as physical, economic, and security capabilities while in the Holy Land. The shift in the meaning of istiṭa’ah narrowly has referred only to economic ability, as influenced by the high costs, the long waiting lists, and a large number of transfers of regular hajj to hajj handled by private travel agents. The shift in the meaning of istiṭa’ah towards the economic ability is due to no other indicator other than the economy that makes any constraints or limitations can be overcome through paid services of other people. Those who have economic ability will get more VIP facilities than those who do not. In terms of lughawi meaning, istiṭa’ah should be understood broadly, not merely physical, non-physical nor economic factors. In Islamic law, the waiting list and security factors can become illat (cause) of a person to be able (istiṭa’ah) to perform Hajj.